The Role of Purchase Interest as A Mediator Between Brand Image, Product Quality and Brand Ambassador on Purchasing Decission Whitelab Skincare in Pati Regency (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The Role of Purchase Interest AS A Mediator Between Brand Image, Product Quality, and Brand Ambassador on Purchasing Decission Whitelab Skincare in Pati Regency. The data collection method used in this study uses a survey by distributing questionnaires to respondents who have met the criteria. Then processed using SmartPLS 3 with a total of 400 respondents. The novelty in this study is that there are additional variables that are different from previous studies and different research locations or places so that the results found are different. The results of this study indicate that brand image, product quality, and brand ambassadors influence purchase interest. Brand image, product quality, and brand ambassadors influence purchase decisions. The results of this study also show that purchase interest also influences purchase decisions. In addition, purchase interest can mediate between brand image, product quality, brand ambassadors and purchase decisions.
Keywords: Brand Image; Product Quality; Brand Ambassador; Purchase Decision; Purchase Interest